THE ROLE OF INTERNAL CONTROLS IN FINANCIAL CONTROLLERSHIP AND TRANSPARENCY FOR ORGANIZATIONAL SUSTAINABILITY - Silva, Karina da Fonseca Inacio (Revista Sistemática, 2022)
This article analyzes the critical integration of controllership, accounting, and compliance as foundational pillars that support the financial sustainability of organizations. It emphasizes how internal controls function as essential tools to ensure transparency, accuracy, and reliability in financial reporting. Key governance mechanisms such as continuous auditing, monitoring systems, and performance reporting are discussed as instruments that reinforce corporate governance and risk management. By promoting ethical practices and regulatory compliance, internal controls enable organizations to build resilience, foster stakeholder trust, and achieve sustainable growth in a complex business environment. The article consolidates recent academic findings and practical insights to illustrate how internal controls underpin sustainable financial management and transparency.